Use of selenium to increase antioxidant activity and water use efficiency in arugula (Eruca vesicaria ssp. Sativa) exposed to drought stress (Research, Society and Development, 2020)
Environmental stress can directly or indirectly affect the formation of reactive oxygen species. Oxidative stress damages cell constituents such as carbohydrates, lipids, nucleic acids and proteins, reducing plant growth, respiration and photosynthesis. In recent decades, evidence has shown that small doses of selenium act as an antioxidant and plant biostimulant, promoting growth and improving resistance to abiotic stress such as drought. As such, the aim of this study was to assess the effect of selenium foliar feeding (0, 150 and 300 ppm) on the antioxidant activity, water use efficiency and yield traits of arugula grown with and without drought stress (50% and 100% ETc) in a protected environment. A randomized block design was used, with a 2x3 factorial scheme and four repetitions. Antioxidant activity increased in treatments with 150 ppm of fertilizer and exposure to drought stress. Plants in these treatments obtained higher water use efficiency, yield and leaf area values than those not submitted to drought stress.